Penemuan Hukum oleh Hakim dalam Perspektif Hukum Progresif - Setyawan, Vincentius Patria (Universitas Muhammadiyah Bima, 2025)
This study aims to explore the concept of judicial lawmaking within the framework of progressive jurisprudence, which emphasizes the dynamic application of law that is responsive to social change and the pursuit of substantive justice. Judicial lawmaking often becomes necessary when legal issues arise that are not sufficiently addressed by existing statutes or case law. In the context of progressive jurisprudence, judges are expected to go beyond mechanical application of legal provisions and to interpret the law in a manner that reflects evolving societal values. This research employs a normative legal methodology, using a doctrinal and interpretative approach to analyze judicial decisions that exemplify progressive legal reasoning. Key rulings in cases concerning human rights, environmental law, and social justice are examined to uncover the progressive legal principles articulated by judges. The findings suggest that in certain instances, judges have successfully exercised judicial creativity, interpreting the law in a way that provides equitable and contextually relevant solutions, even when these decisions diverge from the literal text of the law. Judicial lawmaking in the progressive jurisprudential framework highlights that the law is not a static system but one that is adaptive, evolving, and aimed at ensuring substantive justice.